Testing and evaluation of standoff chemical agent detectors (National Academies Press, 2003)
This Web site is an electronic version of a report that showcases testing and evaluation of standoff chemical warfare agent detectors to certify their suitability and reliability for field applications. Learn about the two major challenges involved as the report discusses and addresses the questions raised by the DoD with respect to the value of testing with simulants and CWAs in chamber and field conditions.